A Review Paper on Identification of Critical Success Factors (CSFs) for Successful Project Management of Construction Projects - Muhammad Nadeem Zia (Journal of Management Practices, Humanities and Social Sciences, 2020)
The study was conducted to write a review paper on the identification of most important factors in order of importance after reviewing various studies on the subject. These factors can serve as a guideline while undertaking any project related to the construction industry. Moreover, various aspects of the project have also been explored regarding key traits of Project Team, Project stakeholders, and Project management practices. These highlighted areas can play an important role in the successful project management of any project related to the construction industry. There are many factors that need to be considered during the course project planning, project execution/implementation, and finishing of the projects. These factors play vital role for on time completion of the construction Project. Out of the numerous factors involved, there are some critical factors which are compulsory to be considered for the success of the construction project. In writing of this review paper, 10 research papers were studied, and 44 factors involved in the construction industry were verified. Upon studying further, only 10 critical factors were finalized, which occurred numerously in the different papers, were considered, and are presented in the table. These 10 critical factors are the ones that decide the fate and success of any construction project. Since it was found that they were repeated in multiple research papers, it shows the importance and significance of the factor in any construction project, which is to be considered. Various review papers are available for software projects but comprehensive review related to construction-related projects and specifically guiding factors concerning project management has not been identified recently. The study will help companies consider the most important factor prior to initiating any project related to construction.